Relationship Between Place Attachment, Place Satisfaction, and Pro-Environmental Behaviour in an Australian National Park - Ramkissoon, Haywantee; Smith, L.; Weiler, B. (Routledge, 2013)
Place attachment is a multidimensional construct comprising place dependence, place affect, place identity, and place social bonding. Yet, studies investigating the relationships between place attachment, place satisfaction, and pro-environmental behaviour have not investigated its pluralistic nature. Using data from 452 visitors to the Dandenong Ranges National Park, Australia, this study investigates these four dimensions of place attachment and their relationships with place satisfaction and proenvironmental behavioural intentions. Findings suggest that the four place attachment constructs are significantly associated with place satisfaction. Results suggest that it is necessary to consider pro-environmental behavioural intentions as a two-factor structure construct, comprising low and high effort pro-environmental behaviour. Place satisfaction is associated with low effort pro-environmental behavioural intentions. Place affect is significantly associated with both types of environmental behavioural intentions. Place identity is not associated with either type of environmental behavioural intentions.Asignificant association is also noted between low effort and high effort pro-environmental behavioural intentions. Practical applications of the study include marketing aimed at encouraging repeat visitation, with sophisticated message development and delivery building emotional attachment, a sense of belonging, and enhanced personal meaning. Heritage interpretation could use affect and emotion to enhance visitor satisfaction and experience, coupled with an outcomes-focused communication plan.